2016
DOI: 10.1161/circresaha.116.306842
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Use and Misuse by the Heart

Abstract: The heart utilizes large amounts of fatty acids as energy providing substrates. The physiologic balance of lipid uptake and oxidation prevents accumulation of excess lipids. Several processes that affect cardiac function including ischemia, obesity, diabetes, sepsis, and most forms of heart failure lead to altered fatty acid oxidation and often also to the accumulation of lipids. There is now mounting evidence associating certain species of these lipids with cardiac lipotoxicity and subsequent myocardial dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
232
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(238 citation statements)
references
References 244 publications
(280 reference statements)
4
232
1
1
Order By: Relevance
“…HFrEF patients had the lowest intramyocardial fat amount. Preclinical cardiac cachexia might explain this finding . Myocardial TG was significantly higher in HFpEF women than in men.…”
Section: Discussionmentioning
confidence: 89%
“…HFrEF patients had the lowest intramyocardial fat amount. Preclinical cardiac cachexia might explain this finding . Myocardial TG was significantly higher in HFpEF women than in men.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies have indicated that diacylglycerol and ceramide, but not TG, are responsible for cardiac lipotoxicity (Schulze et al. ). In addition, several studies have shown protective roles of lipid droplets in cells by storing TGs incorporated from cytotoxic saturated fatty acid (Listenberger et al.…”
Section: Discussionmentioning
confidence: 99%
“…In settings of both T1D and T2D, the heart becomes almost completely reliant upon FAs as a source of energy. Although the mechanisms by which this occurs are (Poornima et al 2006, Goldberg et al 2012, Bayeva et al 2013, Schulze et al 2016). Thus, we will just briefly address the key pathways by which pathological lipid accumulation is thought to contribute toward the development of cardiomyopathy in the setting of diabetes (Fig.…”
Section: Lipid Metabolism and Diabetic Cardiomyopathymentioning
confidence: 99%